THE ROLE OF FISCAL POLICY IN THE SYSTEM OF GOVERNMENT REGULATION OF INVESTING ACTIVITY IN UKRAINE - T. Zatonatska (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
This paper highlights the evolution of approaches to fiscal policy formulation and suggests the appropriate measures on how to provide qualitative changes in the fiscal management of investment activities in Ukraine. The author provides practical proposals on how to create the fiscal space for investments in Ukraine which is aimed to restore the innovation investment model of national economy and to increase the efficiency of budget expenditures.